Caught in the Same Net? Small-Scale Fishermen's Perceptions of Fisheries Interactions with Sea Turtles and Other Protected Species - Panagopoulou, Aliki; Meletis, Zoë A.; Margaritoulis, Dimitris; Spotila, James R. (Frontiers in Marine Science, 2017)
Small-scale fisheries are responsible for high numbers of animals caught as bycatch, such as turtles, cetaceans and seals. Bycatch and its associated mortality is a major conservation challenge for these species and is considered undesirable by fishermen. To gain insights on the impact of bycatch on small-scale fishermen and put it in context with other financial and environmental challenges they face, we conducted questionnaire-based interviews on fishermen working on Crete, Greece. We investigated fishermen’s perceptions of sea turtle and other protected species interactions, and the impacts of such interactions on their profession and livelihoods. Our results indicate a connection between declining fish stocks, related increased fishing effort, and reported increased frequency of interactions between fishermen and sea turtles. Respondents believed that their livelihoods were endangered by industrial fishing and environmental problems, but thought that combined interactions with turtles and other marine megafauna species were a larger problem. Responses suggested that extending compensation to fishermen may be a good conservation intervention. Small-scale fishermen hold a wealth of knowledge about the marine environment and its resources. This may be of help to researchers and policy makers as it could be used to achieve a better managed, sustainable fishery. Including small-scale fishermen in the process of developing regulations will both enhance those regulations and increase compliance with them.